Ethnic Characteristics of Employment and Labor Mobility in Contemporary Russian Studies - Valiakhmetov, Rim M.; Belyakov, Nikolai S. (The New Research of Tuva, 2025)
This article presents a review of Russian scientific publications from the past 25 years devoted to the study of ethnic characteristics of employment and labor mobility among the population of Russia. Based on the overview and analysis of these scientific works, several research groups are identified: the Moscow, Tuvan, and Bashkortostan schools, as well as a number of other research teams and individual authors who are currently actively investigating the ethnic features of employment and labor mobility in Russia. Particular emphasis is placed on studying the ethnic characteristics of employment and labor mobility in the republics of the Russian Federation, especially in Bashkortostan and Tuva. This focus is due to the unique nature of national republics as historically established territories of the joint residence of various ethnic groups, which makes it possible to more fully reveal the specific features inherent to them in the sphere of employment and labor mobility. Solving this research problem has also enabled the authors to identify the most relevant and in-demand directions for future studies in this field—such as accounting for the impact of digitalization and informatization factors on employment and labor mobility among different ethnic groups.